2009
DOI: 10.1111/j.1399-0012.2008.00912.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a renal graft due to recurrence of anti‐GBM disease despite rituximab therapy

Abstract: The recurrence of anti-glomerular basement membrane (anti-GBM) glomerulonephritis (GN) in renal transplants is very rare. We report on a patient that developed acute renal allograft dysfunction due to anti-GBM GN relapse 18 months after transplantation. As plasmaseperation, dose escalation of MMF, steroids and cyclophosphamids did not result in an improvement of the graft function, a therapy with the anti-CD20 antibody Rituximab was established in addition to plasmaseperation, cyclophosphamid and steroids. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
(12 reference statements)
0
21
0
Order By: Relevance
“…Although early case series showed frequent biopsy-demonstrated recurrence in the allograft (up to 50%), 23 reports of recurrent disease leading to renal allograft failure with modern therapeutic approaches are rare. 11,24,25 In 1982, Cameron suggested that recurrence could be reduced to less than 5% if the patient was dialysed for 6-12 months before renal transplantation. 26 However, in the present study, renal allograft survival was comparable between patients with anti-GBM disease ESRD transplanted o1 year vs. X1 year after commencing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although early case series showed frequent biopsy-demonstrated recurrence in the allograft (up to 50%), 23 reports of recurrent disease leading to renal allograft failure with modern therapeutic approaches are rare. 11,24,25 In 1982, Cameron suggested that recurrence could be reduced to less than 5% if the patient was dialysed for 6-12 months before renal transplantation. 26 However, in the present study, renal allograft survival was comparable between patients with anti-GBM disease ESRD transplanted o1 year vs. X1 year after commencing dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The European study also reported a higher frequency of recurrent disease (14%), although this may reflect differences in immunosuppressive use during an earlier era, and the study did not comment on anti-GBM titers and their relationship to timing of transplantation. In the current era, isolated case reports of recurrent disease still exist (79).…”
Section: Kidney Transplantation After Anti-gbm Diseasementioning
confidence: 99%
“…Renal recovery was not observed in either of the patients, and one of the patients developed leukoencephalopathy [23]. Sauter et al reported a case of an anti-GMB disease relapse 18 months after renal transplantation [24]. Rituximab was added after the failure of first-line treatment [24].…”
Section: Anti-gbm Diseasementioning
confidence: 99%